DUKUNGAN KELUARGA DAN KEPATUHAN DIET LANSIA PENDERITA HIPERTENSI DI WILAYAH KERJA PUSKESMAS TUMPAAN - Alfany Natalia Torar; Semuel Tambuwun; Herlina P Memah; Yourisna Pasambo (Jurnal Ilmiah Perawat Manado (Juiperdo), 2020)
Introduction Data obtained from the working area of Puskesmas Tumpaan found that hypertension in the elderly was the first prominent disease in the range of January-December 2017, as many as 465 patients and in 2018 the number of patients was 510. Based on preliminary studies of elderly people with high blood pressure, said their blood pressure often increases because they do not adhere to a diet. Lack of support from family members can influence the compliance behavior of implementing a hypertension diet. The purpose of this study is to find out the relationship between family support and adherence to the diet of elderly people with hypertension in the work area of the Puskesmas Tumpaan in the coastal areas and and mountain areas. This type of research is Correlation Analytic with cross sectional design. The population in this study is the elderly with hypertension. The sampling technique uses proportional random sampling with a total of 84 people divided into 42 people in coastal areas and 42 people in mountain areas and data analysis techniques using the Chi Square test. The results showed that in the coastal areas 31% of respondents with good family support, 40% of respondents had adequate family support and 29% of respondents had less family support while 52% showed adherent diet adherence and 48% adherence to non-adherent diet. The results of the chi-square statistical test (Pearson chi-square) obtained a P-value of 0.008, meaning that the P-value <0.05. The results of the study in the mountain areas of 40% of respondents with good family support, 31% of respondents with adequate family support and 29% of respondents with less family support, 57% showed adherent diet adherence and 43% of adherent diet adherence. The results of the chi-square statistical test (Pearson chi-square) obtained a P-value of 0.021, meaning that the P-value <0.05. The conclusion of this study is that there is a relationship of family support with adherence to the diet of elderly patients with hypertension in both coastal and mountain areas.